The changing nature of Chinese complementary schools in the UK - Li, Xian (2017)
Chinese complementary schools (CCS) play a significant role in transmitting the Chinese language and culture to younger British Chinese generations. Existing research are largely set in Cantonese-dominant CCS, which have characterised long-established UK Chinese communities. However, the last five to ten years have witnessed a demographic change of UK Chinese population and Mandarin is replacing Cantonese as the lingua franca of UK Chinese communities. This research aims to explore the current practices in three CCS and to understand the impacts of UK Chinese demographic change on CCS. Data was collected using ethnographic observation, document collection and semi-structured interviews with teachers, parents and pupils.